Two-dimensional multimode terahertz random lasing with metal pillars - Zeng, Yongquan (2020)
Random lasers employing multiple scattering and interference processes in highly disordered media have been studied for several decades. However, it remains a challenge to achieve a broadband multimode random laser with high scattering efficiency, particularly at long wavelengths. Here, we develop a new class of strongly multimode random lasers in the terahertz (THz) frequency range in which optical feedback is provided by multiple scattering from metal pillars embedded in a quantum cascade (QC) gain medium. Compared with the dielectric pillars or air hole approaches used in previous random lasers, metal pillars provide high scattering efficiency over a broader range of frequencies and with low ohmic losses. Complex emission spectra are observed with over 25 emission peaks across a 0.4 THz frequency range, limited primarily by the gain bandwidth of the QC wafer employed. The experimental results are corroborated by numerical simulations that show the lasing modes are strongly localized.